2007
DOI: 10.1007/s00412-007-0137-1
|View full text |Cite
|
Sign up to set email alerts
|

In vivo modeling of polysumoylation uncovers targeting of Topoisomerase II to the nucleolus via optimal level of SUMO modification

Abstract: Conjugation of SUMO to target proteins is an essential eukaryotic regulatory pathway. Multiple potential SUMO substrates were identified among nuclear and chromatin proteins by proteomic approaches. However, the functional roles of SUMO-modified pools of individual proteins remain largely obscure, as only a small fraction of a given target is sumoylated and therefore is experimentally inaccessible. To overcome this technical difficulty in case of Topoisomerase II, we employed constitutive SUMO modification, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 46 publications
(78 reference statements)
3
30
0
Order By: Relevance
“…However, it is known that, among SUMO substrates, Top1 and Top2 topoisomerases are involved in the maintenance of tandem rDNA array stability [32]. Moreover, we have previously shown that top2ΔC and top2-SNM alleles, with either complete or partial loss of in vivo Top2p sumoylation, respectively [20],[33] (and unpublished data), result in a decrease of the rDNA copy number [11]. Consistent with the role of Top2 sumoylation in rDNA regulation, Top2ΔC ChIP from nocodazole-arrested cells (sumoylation levels of Top2p are maximal in mitosis [33]) showed a strong peak towards the end of the 35S RNA gene, which was not present in wild type (Figure 3A).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…However, it is known that, among SUMO substrates, Top1 and Top2 topoisomerases are involved in the maintenance of tandem rDNA array stability [32]. Moreover, we have previously shown that top2ΔC and top2-SNM alleles, with either complete or partial loss of in vivo Top2p sumoylation, respectively [20],[33] (and unpublished data), result in a decrease of the rDNA copy number [11]. Consistent with the role of Top2 sumoylation in rDNA regulation, Top2ΔC ChIP from nocodazole-arrested cells (sumoylation levels of Top2p are maximal in mitosis [33]) showed a strong peak towards the end of the 35S RNA gene, which was not present in wild type (Figure 3A).…”
Section: Resultsmentioning
confidence: 84%
“…In S. cerevisiae , one prominent subnuclear domain relevant to SUMO biology is the nucleolus, as our previous results showed that the green fluorescent protein (GFP) fusion to Smt3p has a preference for nucleolar localization when deconjugation is impaired [11]. In the present study, we examine the potential cooperation of several chromosomal proteins known to be involved in the stability of ribosomal RNA genes (rDNA).…”
Section: Introductionmentioning
confidence: 95%
“…It is not known whether Top2 is targeted to yeast CENs in an equivalent manner. However, Top2-SUMO fusion proteins can exhibit robust cross-linking to CEN DNA (Takahashi et al, 2006) or accumulate in the nucleolus (Takahashi and Strunnikov, 2007), indicating sumoylation may also regulate yeast Top2 trafficking. In this report, we used the top2-SNM allele to specifically examine functions associated with Top2 SUMO modification, comparing top2-SNM strains to catalytically inactive top2-4 mutants.…”
Section: Discussionmentioning
confidence: 99%
“…At the minimum, our findings linking a selective SUMO chain defect to aberrant gene repression suggest that polySUMO modification support a specific chromatin signaling function distinct from that of the monoSUMO modification of WASp. Although the causality of this association remains speculative, emerging evidence linking poly-SUMO chain defects to impaired chromatin-to-nucleolar targeting and DNA instability, 73 altered chromatin organization and transcriptional repression, 28 and Alzheimer's disease 74 together propose a physiologically relevant role for WASp polySUMO chains in immunity.…”
Section: Discussionmentioning
confidence: 99%